Methoxychlor induces oxidative stress and impairs early embryonic development in pigs - Geng, Zhaojun; Jin, Yongxun; Quan, Fushi; Huang, Siyi; Shi, Shuming; Hu, Bing; Chi, Zhichao; Kong, Ilkeun; Zhang, Mingjun; Yu, Xianfeng (Frontiers in Cell and Developmental Biology, 2023)
Methoxychlor (MXC) is an organochlorine pesticide (OCP) that was formerly used worldwide as an insecticide against pests and mosquitoes. However, MXC is not biodegradable and has lipophilic charac-teristics; thus, it accumulates in organisms and affects reproductive function. MXC, as an estrogenic compound, promotes oxidative stress, induces oxidative stress damage to ovarian follicles, and causes miscarriages and stillbirths in females. In this research endeavor, our primary objective was to explore the ramifications of MXC regarding the developmental processes occurring during the initial stages of embryogenesis in pigs. Reactive oxygen species, mitochondrial membrane potential, mitochondrial copy number, cellular apoptosis, DNA damage, pluripotency, and genes associated with apoptosis were all subject to examination in this study. The results showed that early embryos exposed to MXC had a significantly lower cleavage rate, blastocyst rate, hatching rate, and total cell count compared with the control group. It was also of note that MXC not only increased the levels of reactive oxygen species (ROS), but also decreased the mitochondrial membrane potential (ΔΨm) and mitochondrial copy number during the development of early embryos. In addition, after MXC treatment, blastocyst apoptosis and DNA damage were increased, decreased cell proliferation, and the expression of pluripotency-related genes SOX2, NANOG, and OCT4 was down-regulated, while the expression of apoptosis-related genes BAX/BCL-2 and Caspase9 was up-regulated. These data show that MXC may suppress early embryonic development through the induction of oxidative stress.